Habitat, insect composition and enviromental parameters that influence on ranging behaviour of Aerodramus fuciphagus Thunberg at Kuala Langat district, Selangor, Malaysia - Burhanuddin, Maisarah (2016)
Edible nest (EN) swiftlets are widely known for their unique edible nest, however, their ecology and behavior are still largely undiscovered. This research has attempted to understand the ecology and the ranging behavior of Aerodramus spp, by mapping out favorable feeding spots and identifying insect’s species and diversity therein. The study site was located in the Kuala Langat district, Selangor, Malaysia, over a two year duration I.e. from March 2013 to March 2015. The en swiftlets successfully captured, tagged with transmitters and radio-tracked on a 4-wheel drive vehicle. Within the traceable range, based on the kernel analysis method, seven sampled swiftlets had an average home range size of 6437.47 ha. A corresponding average core area size of 1687.06 ha, and average furthest flying distance flown from the swiftlet range of 11.78 km. They were mostly found roaming and foraging in riverbanks area; which was the preferred habitat based on the Jacob index value of 0.3439. Within these areas, insect trappings yielded predominantly high numbers of hymenopterans (41.78%) followed by almost equal distributions of dipterans (33.34%). Other habitats such as residential area, oil palm older than 5 years old, oil palm younger than 5 years old and grassland also shows high number of hymenopterans and dipterans. Pearson correlation shows both the 50% core area size and the 95% foraging area size was negatively correlated to the wind velocity with values of r = 0.8067, p= 0.9854 and r=0.8205, p=0.9883, respectively. The average flying velocity was positively correlated to the wind speed (r=0.8423, p<0.05). This suggest that swiftlet fly in the downwind direction and the higher wind velocity aid in the foraging effort of the EBN swiftlet thereby reducing their measurable foraging/home range size. All other parameters tested I.e. light intensity (r = 0.7286, p = 0.9682), temperature (r = 0.0522, p = 0.5443), humidity (r = 0.1062, p = 0.4104) and API (r = 0.0245, p = 0.4784) (atmospheric particle index - a quantitative measure of haze) have no influence on the flying speed of the swiftlet. This is an indication that apart from wind speed all other environmental factors measured in this study will not impede on the movement of the swiftlet. This was also substantiated by the lack of correlation between light intensity, temperature, humidity and API on both the home range and core area size of the EBN swiftlets. We can conclude that EBN swiftlets are designed to hunt in all weather conditions and they take advantage of wind conditions to facilitate aerial hunting of insect prey.